2014
DOI: 10.18546/lre.12.1.10
|View full text |Cite
|
Sign up to set email alerts
|

International academic franchises: Identifying the benefits of international academic franchise provision

Abstract: This paper is an exploratory study of the benefits that institutions of higher education can gain when entering into partnerships of academic franchising, an international activity which has been increasing in popularity over the past few decades. The paper looks at the current literature on academic franchising and then goes on to study, through case studies and direct observation, franchising from the perspective of four different institutions in four different countries. The paper reveals that very often t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Along with many other studies (e.g. Mellors‐Bourne et al, 2015: Ramsey & Lorenz, 2016), Pon and Ritchie's (2014) study did not incorporate the students’ perspective but did support the general belief that with the increase in globalisation there is a need for students to develop a more international outlook during their programme of study to enhance their future employability.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Along with many other studies (e.g. Mellors‐Bourne et al, 2015: Ramsey & Lorenz, 2016), Pon and Ritchie's (2014) study did not incorporate the students’ perspective but did support the general belief that with the increase in globalisation there is a need for students to develop a more international outlook during their programme of study to enhance their future employability.…”
Section: Introductionmentioning
confidence: 87%
“…However, Pon et al (2011) comment that in the context of TNHE, research into IAFs is often integrated as part of another study and published within the more general, wider internationalisation framework or TNHE, remains true. Pon and Ritchie (2014) suggested that for an IAF to be created both franchisor and franchisee must proactively want to develop collaborative programmes primarily to enhance their status and/or image, and increase income. Along with many other studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The trend towards international alliances has applied to the industry of higher education and particularly business schools. Though not clearly defined in the Higher Education Industry, (Saffu and Mamman, 1999; Li et al , 2011), strategic alliances are part of the development strategy to support business schools’ cross-border activities (Bennett and Kottasz, 2011; Pon and Ritchie, 2014; Guillotin and Mangematin, 2015; Jongbloed, 2015). They are seen as a means to access not only resources, but also market shares (Li et al , 2011), thus “allowing each party in their relevant organisations to collaborate and jointly create new products, new processes or new ideas” (Baden-Fuller and Ang, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sharma continues by stating that business organisations have used networks in the past and that this pattern has the greatest potential to succeed in the future for all types of organisations including educational institutions. In the twenty-first century, we see institutions of higher education forming networks and alliances with institutions from other countries to deliver the academic programmes (Pon and Ritchie, 2014) through for example, the forming of academic franchising and collaborative provision. Bennett and Kottasz (2011) sum it up by arguing that internationalisation includes:[…] a plethora of tasks, organizational and funding arrangements, and strategic decisions […] including for example, international franchising, curriculum internationalisation, research collaborations, cross-border joint ventures, the establishment of campuses in other countries, faculty and student exchange programmes and the recruitment of lecturers with international experience and competences.…”
Section: Cooperative Approaches and Internationalisation Of Business Schoolsmentioning
confidence: 99%
“…Using an approach for data collection in bilingual situations similar to that used in (Pon, Lichy, and Sheard ; Pon and Ritchie ), and due to the international context of the research, it was necessary to conduct the mind mapping exercise in English and French so as not to limit students' free expression through limited knowledge of the foreign language. When data was collected in French, it was translated into English by one of the authors who is not only fluent in both languages but is also a professor of management.…”
Section: Approachmentioning
confidence: 99%